Grazing intensity on the plant diversity of alpine meadow in the eastern Tibetan plateau - Wu Ning; Liu Jian; Yan Zhaoli (Rangifer, 2004)
Because ofthe remoteness and harsh conditions of the high-altitude rangelands on the eastern Tibetan Plateau, the relationship between yak grazing and plant diversity has not been so clear although livestock increase was thought as the main issue leading to the degradation of rangeland. In the debate of rangeland degradation, biodiversity loss has been assumed as one of the indicators in the last two decades. In this paper authors measured the effects of different grazing intensities on the plant diversity and the structure of Kobresia pygmaea community in the case-study area, northwestern Sichuan. The results indicated that plant diversity of alpine meadow has different changing trends respectively with the change of grazing intensity and seasons. In June the highest plant diversity occurred in the intensively grazed (HG) plots, but in July and September species biodiversity index of slightly grazed (LG) plots is higher than other experimental treatments. In August the intermediate grazed (IG) plots has the highest biodiversity index. Moreover, it was found that intensively grazing always leads to the increase of plant density, but meanwhile the decrease of community height, coverage and biomass. Over-grazing can change the community structure and lead to the succession from Kobresia pygmaea dominated community to Poa pratensis dominated. Analyzing results comprehensively, it can be suggested that the relationship between grazing intensity and plant diversity is not linear, i.e. diversity index is not as good as other characteristics of community structure to evaluate rangeland degradation on the high altitude situation. The change of biodiversity is so complicated that it can not be explained with the simple corresponding causality.